2020
DOI: 10.1149/1945-7111/aba513
|View full text |Cite
|
Sign up to set email alerts
|

High Voltage Stable Li Metal Batteries Enabled by Ether-Based Highly Concentrated Electrolytes at Elevated Temperatures

Abstract: Li metal batteries (LMBs) employing high voltage cathodes are necessary to attain high energy density. Although highly concentrated ether-based electrolytes (e.g. 4 M LiFSI/DME) can yield stable cycling of Li metal anodes, their high voltage instability fosters incompatibility with high voltage cathodes. In this work, the temperature dependence of fresh cell performance, Li Coulombic efficiency (CE), and cycling stability of LMBs in highly concentrated LiFSI/DME electrolytes was explored. Elevated temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 51 publications
(85 reference statements)
0
25
0
Order By: Relevance
“…Concentrated LiTFSI- and LiFSI-based electrolytes are well known for their beneficial effect on the cycling stability of Li metal-based batteries. ,,, Nilsson et al reported that a LiTFSI:EC 1:6 electrolyte was superior to reference electrolytes when cycled in symmetrical Li-Li cells and anode-free Li-Cu cells. Here, the electrolytes are tested in Si/graphite-based cells with a Li counter electrode.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Concentrated LiTFSI- and LiFSI-based electrolytes are well known for their beneficial effect on the cycling stability of Li metal-based batteries. ,,, Nilsson et al reported that a LiTFSI:EC 1:6 electrolyte was superior to reference electrolytes when cycled in symmetrical Li-Li cells and anode-free Li-Cu cells. Here, the electrolytes are tested in Si/graphite-based cells with a Li counter electrode.…”
Section: Resultsmentioning
confidence: 99%
“… 11 In other studies, improved oxidation resistance of different HCE systems has been reported, and it was shown that better electrochemical performance can be achieved in full cells or half cells also with layered oxide cathode materials such as LiNi x Mn y Co 1– x – y O 2 (NMC). 18 26 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the discharge experiment after storage at 65 °C for 7 days showed that the capacity retention of the mixed salt is ≈96%, much better than that of LiPF 6 (≈60%). [51] The combination of LiBF It is able to passivate aluminum foil when the voltage reaches 4.2 V. [61] Leng et al [62] adopted an ether-based electrolyte with a high concentration of LiFSI and added suitable additives to enhance the stability of the electrolyte under high temperatures and high pressure. The capacity retention of LiNi 0.6 Co 0.2 Mn 0.2 O 2 cells could reach 80% after 175 cycles at 60 °C.…”
Section: Lithium Saltmentioning
confidence: 99%
“…Zhang's group [73] investigated a high temperature tolerant electrolyte using a mixed solvent consisting of fluoroethylene carbonate (FEC) and tetraethylene glycol dimethyl ether with dissolved LiFSI and LiNO 3 . The Li||LFP battery using this electrolyte undergoes 100 cycles with a capacity [46] Li||LiMn 2 O 4 1.0 m in LiBOB EC/PC(1:1 volume ratio) 60 0.5 C, 3.5-4.2 V, 50 cycle [47] Li||LiFePO 4 0.7 m LiBOB in SL/DMS(1:1 volume ratio)0.7 m LiBOB in SL/DES(1:1 volume ratio) 60 0.5 C, the 100th cycle: capacity retention 94.0%; the 100th cycle: capacity retention 66.5% [48] LiFePO 4 1.0 m LiBF 4 /LiBOB (9:1 mole ratio) in PC/EC/EMC (1:1:3 volume ratio) 90 ≈3.0 V, provide up to ≈30% of capacity [50] Li||LiMn 2 O 4 1 m LiDFOB in PC/EC/EMC(1:1:3 volume ratio) 60 0.5 C, 2.75-4.2 V, the 100th cycle: capacity retention 87.5% [53] Li||LiNi 0.8 Mn 0.1 Co 0.1 O 2 0.8 m LiPF 6 + 0.2 m LiDFOB in EC/EMC (3:7 volume ratio) 60 0.5 C, 2.8-4.3 V, the 100th cycle: capacity retention 89% [55] Li||LiCoO 2 0.2 m LiDFOB + 0.8 m LiBF 4 in PC/EC/EMC (1:1:3 volume ratio)+ 5% FEC 60 1 C, 3-4.2 V, the 100th cycle: capacity retention 93.5% [56] LiCoO 2 0.4 m LiDFOB + 0.6 m LiTFSI in EC/PC(1:1 volume ratio) 80 0.5 C (1.2 mA cm −2 ), 3.0-4.2 V, the 100th cycle: capacity retention 90% [58] Li||LiNi 0.6 Mn 0.2 Co 0.2 O 2 LiFSI/DME (1:1.2 mole ratio) + 1 wt.% TAP 60 1/3 C charge,1 C discharge, 2.8-4.3 V, the 64th cycle: capacity retention 80% [62] Li||LiNi 0.5 Mn 1.5 O 4 LiFSI/SN/AN (1:0.5:0.5 mole ratio) + 0.25 wt.% LiNO 3 + 0.35 wt.% InF 3 100 0.1 C, 3.5-4.9 V, 20 cycles [71] Li||LiFePO, 4 Li||LiNi 0.5 Mn 0. 90°C, more than 100 cycles [72] Li||LiFePO 4 1 m LiPF 6 in EC/EMC + TPPO/LiNO 3 70 0.3 C (1 C = 170 mAh g -1 ), the 50th cycle: capacity 129.6 mAh g −1 , capacity retention ≈80% [74] Li||CF x 1 m LiClO 4 in TTE/DME/PC(2:2:1 volume ratio) 55 3000 mA g −1 , the middle value of voltage: 2.22 V, power density: 6673 W kg −1 , energy density 1475 Wh kg −1 [81] Li||LiNi 0.5 Co 0.2 Mn 0.3 O 2 1.3 m LiDFOB in TEP/HFE (1:2.5:2 molar ratio) 70 0.5 C, 2.8-4.5 V, the 100th cycle: Coulombic efficiency ≈99%, capacity retention ≈93.2% [82] Li||LiNi 0.5 Mn 1.5 O 4 0.5 m LiPF 6 in FEC/DMC/TTE (1:4:5 volume ratio) 55 1 C, the 170th cycle: capacity retention 80.5% [83] Li||LiFePO 4 1.0 m LiTFSI in DOL/DME(1:1 volume ratio) + 1 wt.% LiNO 3 60 1 C (170 mAh g -1 ), the 100th cycle: capacity 146 mAh g −1 [87] Li||LiNi 1/3 Mn 1/3 Co 1/3 O 2 1 m LiPF 6 in FEC + 2 wt.% LiTDI 60 0.5 C, 3.0-4.2 V, 60 cycles [88] Li||S 5 m LiTFSI +LiFSI in G4 + TTE 60 0.2 C, 1.0-3.0 V, the 100th cycle: capacity 666 mAh g −1 [89] Li||LiNi 0.8 Co 0.2 O 2 1 m Li...…”
Section: Solventsmentioning
confidence: 99%